2022
DOI: 10.1007/s12630-022-02299-w
|View full text |Cite
|
Sign up to set email alerts
|

Avoidable intensive care unit resource use and costs of unvaccinated patients with COVID-19: a historical population-based cohort study

Abstract: Purpose SARS-CoV-2 vaccines have been proven effective at preventing poor outcomes from COVID-19; however, voluntary vaccination rates have been suboptimal. We assessed the potential avoidable intensive care unit (ICU) resource use and associated costs had unvaccinated or partially vaccinated patients hospitalized with COVID-19 been fully vaccinated. Methods We conducted a retrospective, population-based cohort study of persons aged 12 yr or greater in Alberta (2021 pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 17 publications
(19 reference statements)
2
14
0
Order By: Relevance
“…First, the study by Bagshaw et al used "publicly available age-stratified aggregate data on COVID-19 infections, vaccination status, and health service use provided by Alberta Health." 1 A major error in this data was misattribution of vaccination status. Those single-or double-dose vaccinated within 14 days were considered in the unvaccinated or partially vaccinated group respectively.…”
Section: Effect Of Vaccination On Icu Admissions Were Over-estimatedmentioning
confidence: 99%
See 4 more Smart Citations
“…First, the study by Bagshaw et al used "publicly available age-stratified aggregate data on COVID-19 infections, vaccination status, and health service use provided by Alberta Health." 1 A major error in this data was misattribution of vaccination status. Those single-or double-dose vaccinated within 14 days were considered in the unvaccinated or partially vaccinated group respectively.…”
Section: Effect Of Vaccination On Icu Admissions Were Over-estimatedmentioning
confidence: 99%
“…The authors in Bagshaw et al concluded that their findings "have important implications for discourse on the relative balance of increasingly stringent public health protection (restrictions), including mandatory vaccination policies, and the sustainability and function of health system infrastructure and capacity during the ongoing COVID-19 pandemic." 1 We are not so sure.…”
Section: Policy Implications At Best Unclearmentioning
confidence: 99%
See 3 more Smart Citations